2018
DOI: 10.1186/s12957-018-1326-5
|View full text |Cite
|
Sign up to set email alerts
|

A case of adrenocortical carcinoma accompanying secondary acute adrenal hypofunction postoperation

Abstract: BackgroundAdrenocortical carcinoma (ACC) is a rare, heterogeneous malignancy with a poor prognosis. ACCs are classified as functioning and non-functioning. The pathogenesis of ACC remains elusive, and diagnosis of ACC is currently based on pathology. In the absence of other effective approaches, surgical resection is the preferred treatment option.Case presentationHere, we report a case of ACC in the retroperitoneum. The patient underwent radical adrenalectomy and remained disease-free throughout a 6-month fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Taken together, these data indicate that the substances described in the leaves of N. procerum proved to be efficient in modulating significant responses mediated by macrophages. This can be a potential alternative as a therapeutic agent applied www.nature.com/scientificreports www.nature.com/scientificreports/ were also carried out to evaluate the cytotoxic activity of in vitro cultured N. procerum Lindm against H295R cell line, a carcinoma with rare, heterogeneous malignancy and a very poor prognosis 76 .…”
Section: Chlorophyll Quantification Leaves Ofmentioning
confidence: 99%
“…Taken together, these data indicate that the substances described in the leaves of N. procerum proved to be efficient in modulating significant responses mediated by macrophages. This can be a potential alternative as a therapeutic agent applied www.nature.com/scientificreports www.nature.com/scientificreports/ were also carried out to evaluate the cytotoxic activity of in vitro cultured N. procerum Lindm against H295R cell line, a carcinoma with rare, heterogeneous malignancy and a very poor prognosis 76 .…”
Section: Chlorophyll Quantification Leaves Ofmentioning
confidence: 99%
“…As far as we know, adrenal hypofunction is a very rare phenomenon after TACE, as it has not been reported so far. Adrenal hypofunction often occurs after adrenal gland removal, and related studies have shown that over 23% of patients with adrenal tumor resection have acute adrenal hypofunction[ 7 , 14 , 15 ]. Although adrenal cortical cancer is divided into functional and nonfunctional, both types of ACC may cause acute adrenal hypofunction.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal hypofunction often occurs after adrenal gland removal or long-term use of glucocorticoids, etc [12][13]. As far as we know, adrenal hypofunction is a very rare phenomenon after arterial duct embolization, and it has not been reported so far.…”
Section: Discussionmentioning
confidence: 99%